User Tag List Thanks:  0 Likes:  0

1. 3x+68=9x+18 x=?

This is my daughters home work, she nor me can do this one.  can anyone help.   Reply With Quote

2. Used this http://numberz.co.uk/ES.html  Reply With Quote

3. Simplifying
3x + 68 = 9x + 18x

Reorder the terms:
68 + 3x = 9x + 18x

Combine like terms: 9x + 18x = 27x
68 + 3x = 27x

Solving
68 + 3x = 27x

Move all terms containing x to the left, all other terms to the right.

Add '-27x' to each side of the equation.
68 + 3x + -27x = 27x + -27x

Combine like terms: 3x + -27x = -24x
68 + -24x = 27x + -27x

Combine like terms: 27x + -27x = 0
68 + -24x = 0

Add '-68' to each side of the equation.
68 + -68 + -24x = 0 + -68

Combine like terms: 68 + -68 = 0
0 + -24x = 0 + -68
-24x = 0 + -68

Combine like terms: 0 + -68 = -68
-24x = -68

Divide each side by '-24'.
x = 2.833333333

Simplifying
x = 2.833333333  Reply With Quote

4. that was my quick working out, it could be wrong as its been a long time since i used google lol  Reply With Quote

5. Thanks guys, I'll give her these answers   Reply With Quote

6.  Originally Posted by merikiito Simplifying
3x + 68 = 9x + 18x

Reorder the terms:
68 + 3x = 9x + 18x

Combine like terms: 9x + 18x = 27x
68 + 3x = 27x

Solving
68 + 3x = 27x

Move all terms containing x to the left, all other terms to the right.

Add '-27x' to each side of the equation.
68 + 3x + -27x = 27x + -27x

Combine like terms: 3x + -27x = -24x
68 + -24x = 27x + -27x

Combine like terms: 27x + -27x = 0
68 + -24x = 0

Add '-68' to each side of the equation.
68 + -68 + -24x = 0 + -68

Combine like terms: 68 + -68 = 0
0 + -24x = 0 + -68
-24x = 0 + -68

Combine like terms: 0 + -68 = -68
-24x = -68

Divide each side by '-24'.
x = 2.833333333

Simplifying
x = 2.833333333
Somehow using the word "Simplifying" does not compute with me!!

Glad my homework was not this hard.... when i actually did it!!  Reply With Quote

7. lol i thought it was just x=2 as in 32+68 is the same as 92+18 therefore x is 2. thats why i didnt finish school i suppose, the above answer seems alot more convincing even although i didnt understand any of it   Reply With Quote

8.  Originally Posted by merikiito Simplifying

Reorder the terms:
68 + 3x = 9x + 18x

Combine like terms: 9x + 18x = 27x
68 + 3x = 27x

Solving
68 + 3x = 27x

Move all terms containing x to the left, all other terms to the right.

Add '-27x' to each side of the equation.
68 + 3x + -27x = 27x + -27x

Combine like terms: 3x + -27x = -24x
68 + -24x = 27x + -27x

Combine like terms: 27x + -27x = 0
68 + -24x = 0

Add '-68' to each side of the equation.
68 + -68 + -24x = 0 + -68

Combine like terms: 68 + -68 = 0
0 + -24x = 0 + -68
-24x = 0 + -68

Combine like terms: 0 + -68 = -68
-24x = -68

Divide each side by '-24'.
x = 2.833333333

Simplifying
x = 2.833333333
I think you misread the question...

its 3x + 68 = 9x + 18 not 3x + 68 = 9x + 18x

the last x 'x=?' signifies they want to solve for x

3x + 68 = 9x + 18

68 - 18 = 9x - 3x

50 = 6x

50/6 = x

x= 8.33  Reply With Quote

9.  Originally Posted by merikiito Simplifying
3x + 68 = 9x + 18x

Reorder the terms:
68 + 3x = 9x + 18x

Combine like terms: 9x + 18x = 27x
68 + 3x = 27x

Solving
68 + 3x = 27x

Move all terms containing x to the left, all other terms to the right.

Add '-27x' to each side of the equation.
68 + 3x + -27x = 27x + -27x

Combine like terms: 3x + -27x = -24x
68 + -24x = 27x + -27x

Combine like terms: 27x + -27x = 0
68 + -24x = 0

Add '-68' to each side of the equation.
68 + -68 + -24x = 0 + -68

Combine like terms: 68 + -68 = 0
0 + -24x = 0 + -68
-24x = 0 + -68

Combine like terms: 0 + -68 = -68
-24x = -68

Divide each side by '-24'.
x = 2.833333333

Simplifying
x = 2.833333333     Reply With Quote

10. Yup sorry as jimbojetset says, she needs to know what X equals, I dont understand any of this stuff    Reply With Quote

Page 1 of 3 123 Last There are currently 1 users browsing this thread. (0 members and 1 guests)